Thursday

April 24, 2014

April 24, 2014

Posted by **Em** on Sunday, January 27, 2013 at 3:16pm.

(a) Find the average value of f.

(b) Find c such that f(average) = f(c).

- Math -
**Reiny**, Sunday, January 27, 2013 at 4:41pmaverage value

= 1/(3-0) ∫(2x^2 - 8x + 9) dx from x = 0 to x = 3

= (1/3) [(2/3)x^3 - 4x^2 + 9x[ from 0 to 3

= (1/3) (18 - 36 + 27 - 0 )

= 3

b)

f(c) = f(3)

2c^2 - 8c + 9 = 18 - 16 + 9

2c^2 - 8c -2 = 0

c^2 - 4c - 1 = 0

c = (4 ± √20)/2

= 2 ± √5

**Related Questions**

math, beginning algebra - how do you solve this i've tried many ways and i ...

Business Calculus - The indefinite integral, or which call the "antiderivative...

Math - I need help with figuring out the equation 5(2x+3)-8x=7 5(2x+3)-8x=7 10x+...

Calculus - 22. Divide the expression before differentiating. F(x) = (8x^3 - 1...

Math- Completely confused! - Simplify each expression (where possible) and ...

math - The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct? [(2x...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

math - how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look ...

Algebra - Which equation could be used to find the dimensions of a room that has...

Math correct - Subtract.. (8x^4+5x^3-6)-(2x^2-2x+6) I got 8x^4+5x-2x^2+2x-12 ...